'Here mirth and merchandise are mix'd': buying and selling at the English provincial fair reconsidered. Issue 3 (2nd September 2019) - Davidson, Jessica
ABSTRACT: Fairs were widely visited in this period for both business and entertainment, and yet their place in the histories of retailing and consumption has been limited. This article presents a renewed analysis of the commercial role of fairs in England in the long eighteenth century. Using a case study of Bristol's St James's Fair, from which a particular wealth of archival evidence remains, it explores how fairs were organised, who traded at these events, and what strategies were used to attract potential customers. Fairs emerge as enduring places of trade whose activities made a significant impact on the businesses of both itinerant traders and those who otherwise traded out of shops. A study of fairs opens avenues of renewed enquiry into the patterns and practices of distribution and the way in which the market for goods was linked to the market for services, entertainment, or agricultural products.